COMPARAÇÃO DA EFICIÊNCIA OCLUSAL DO TRATAMENTO ORTOPÉDICO COM O REGULADOR DE FUNÇÃO FRÄNKEL-2 E BIONATOR DE BALTERS POR MEIO DO ÍNDICE PAR - Melo Júnior, Djalmyr Brandão de Carvalho (2010)
The objective of this retrospective study was to compare the occlusal efficiency of orthopedic treatments using the Fränkel-2 regulator (RF 2) and Balters Bionator functional appliances, treated during different dental development stages, and compare them to a control group. The sample consisted of 45 documented records, belonging to the Dental School graduate program with a concentration area in orthodontics at the Methodist University of São Paulo. All records featured an initial Class II division 1 bilateral malocclusion. Of these, 15 patients were treated with the Bionator (group 1), with average initial age of 8.56 years and 80% of cases in dental development stage-2 (DS 2); 15 patients were treated with RF 2 (group 2), with average initial age of 10.71 years and 80% of cases in dental development stage -3 (DS 3); and a control group with 15 patients (group 3), with average initial age of 10.03 years and with dental development stage compatible both with groups 1 and 2. The groups were divided into two phases, according to the evaluation period: T1: beginning of treatment, and T2: final treatment, totaling 90 pairs of models. The occlusal evaluations were performed in plaster models, using the PAR index with the aid of the PAR ruler and a properly calibrated digital micrometer caliper. For intergroup comparison, ANOVA and Tukey test were used. The severity of the malocclusions (INITIAL PAR) was similar in all groups; however, the final PAR index showed a statistically significant difference, in which the percentile reduction for the PAR index was 20.72% for group 1, 60.06% for group 2, and no significant difference in the final PAR index for group 3. The present study concludes that the treatment for Class II division 1 malocclusion is more efficient when is begins during dental development stage-3 (DS 3) than in dental development stage-2 (DS 2). Moreover, importance is given to a more prolonged use of the dental appliance, as patients in group 2 showed better occlusal results.(AU)